Evaluation of 25-year-old afforestation's of loblolly pine, black alder, velvet maple and chestnut leaved oak in Radar Poshteh area of Guilan province - A. Ebrahimi Ashbella; M.M. Fallahchai; A. Salehi; A.A. Soltani Tolarood (مجله جنگل ایران, 2022)
Afforestation is one of the most important tools in creating green cover and providing wood supply. The aim of current study was to investigate the growth and performance of 25-year-old afforestation's in the Radar-Poshteh region of ​​Guilan province. In this study, eight sample plots of 400 square meters in four 3.5-hectare stands of maple, black alder, chestnut leaved oak and loblolly pine were executed by randomized systematic method and within each sample plot, diameter, height, trunk length without branches, large and small diameter of the crown were measured. Litter depth was also measured at ten points in the sample plots with a ruler. Also, the quality of tree trunks was divided into three categories: grade 1, 2 and 3. Using the collected data, the most important quantitative and qualitative indicators of the four stands were extracted and statistically compared. Also, the biomass of the trees was estimated using the reported allometric equations for the studied species. Based on the results, the highest average diameter (33.42 cm), diameter growth (1.23 cm), highest basal area (78.43 m2/ha), volume (763.98 m3/ha), biomass (971.5 ton/ha), grade 1 trunks (92%), litter thickness (8.6 cm) and the lowest height form factor (0.78) were obtained for loblolly pine stand. Among the native broadleaf species, the highest volume and biomass were calculated with 458 m3 and 520.75 ton/ha for alder species, respectively. Therefore, loblolly pine due to its high production (Controlled in non-forest lands) and chestnut leaved oak due to its high yield along with the production of high quality timbers are recommended for afforestation in Guilan province.